PERAN PENDIDIKAN IPS DALAM MENGEMBANGKAN SIKAP TOLERANSI SISWA KELAS VIII DI SMPN 6 GARUT - Asep Nurozab; Tetep; Yana Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of Social Studies (IPS) education in shaping and developing tolerance attitudes among eighth-grade students at SMPN 6 Garut, as well as to identify the obstacles faced in its implementation. This research employs a qualitative method with a literature study approach. Data were collected from various sources, including books, scientific journals, and research articles related to social studies education and the development of tolerance attitudes. The data collection technique used content analysis, while data analysis was conducted by reviewing, comparing, and synthesizing relevant literature. The results indicate that Social Studies education plays a significant role in developing students' tolerance attitudes through understanding social diversity, interaction in the learning process, and the integration of character values such as empathy, cooperation, and mutual respect. The teacher’s role as a facilitator and role model is also crucial in shaping students' tolerance attitudes. In addition, a supportive school environment contributes to the internalization of tolerance values. However, several obstacles were identified in its implementation, including differences in students' backgrounds, the influence of social media, limited variation in teaching methods, and the lack of optimal integration of character education in Social Studies learning. To overcome these challenges, several efforts are required, such as implementing more interactive and varied teaching methods, improving teachers' competencies, creating an inclusive school culture, and strengthening collaboration between schools and parents. In conclusion, Social Studies education has an important role in fostering students' tolerance attitudes, but it requires integrated support to achieve optimal outcomes.